The reality of the Iraqi woman after the changes that took place on 9/4/2003 - Ismail, Donia Jalil (Al-Adab Journal, 2015)
Discussion Dealt WithThe Subject OfThe Reality OfIraqi WomenAfterThe Changes That HaveOccurred In The9/4/2003, And That TheIssue Of WomenIs The Issue OfCommunityThere Is No DoubtThat WomenElement OfSociety AndBear The Largest BurdenIn The Progress OfLifeAnd StabilityAreInfluencing FactorAnd EffectiveInThe Productivity OfGenerationsAnd TheAssociatedStatus Of WomenConditionsTheMotiveOf CivilizationAndCultural Life Of Society.The Importance OfResearchOf Women'sActive RoleIn The Provision OfCommunityAndThis Role IsIncreasingly ImportantIf TheWomanHas EnjoyedA RespectableStatusIn The Society.The Research AimsToIdentify The Reality OfIraqi WomenVariableFromThe Work AreaAnd Within TheAspects OfSocial, Economic AndPolitical. TheResearch FoundThe Following Results:That TheValues​​, Traditions And Customs Related To TheWeakPosition Of WomenIn SocietyAnd This Is WhatMakes ItDoes Not TakeItselfThat Must BeEnjoyed BySocietyAsHalf.That There Is APresenceFor WomenWithinThe Political Process, But This AttendanceMightWeaken OrFadeDepending On TheWeakness OfIts Position In TheCommunity.There Is StillA Negative PerceptionIn The CommunityAboutWomen's WorkOutside The HomeDespite The Fact ThatTheir WorkLeads ToSupport TheMen AndFurther Improve TheEconomicSituation Of The Family.There Is A DifferenceIn TheMethods OfDifferentiationAndSocializationAmongMales And Females, Which MakesMalesد. معن خليل العمر، علم اجتماع الأسرة ، دار الشروق ،عمان ،ص170، 1994.فوزية العطية، المرأة والتغيير الاجتماعي في الوطن العربي ، الخليج للطباعة، الكويت، ص83، 1983.احمد زكي بدوي، معجم مصطلحات العلوم الاجتماعية، مكتبة لبنان، بيروت،ص382، 1977.عدنان مسلم، الشباب والتغير الاجتماعي، مجلة شؤون اجتماعية تصدر عن جمعية الاجتماعيين، الشارقة،ص88، 1999.عبد الهادي ألجواهري، قاموس علم الاجتماع، حرره وراجعه الدكتور محمد عاطف غيث، التغير الاجتماعي، الهيئة ExcelThroughTheir UpbringingTo OccupySocial StandingIn The Community. TheSearchCame OutWith The Following Recommendations: DirectingMembers Of The CommunityTo The Importance OfWomen's StatusAndRole In SocietyBy ChangingThe Traditional View.Necessity Of ActivatingThe Roles OfWomenIn The VariousMinistries AndEconomic InstitutionsThroughFinancial IncentivesAnd MoralTo Them.Community InstitutionsNeed To Adopt AFormalValues ​​AndPositiveSocial Normsthat helptoraise the statusof women in society